Perlindungan Hukum Terhadap Orang Utan Dari Perdagangan Ilegal - Firman Bagus Prasetyo; Rahtami Susanti; Bayu Setiawan (Universitas Muhammadiyah Purwokerto, 2019)
Illegal trade in protected animals, including orangutans, is still rife in Indonesia, resulting in a decline in population from year to year. This study aims to analyze the legal protection of orangutans from illegal trade, based on Law Number 5 of 1990 concerning Conservation of Living Natural Resources and their Ecosystems and their inhibiting factors. The approach to the problem that will be used in this research is a normative juridical approach. The results of the study show that first, the number of orangutan populations has decreased due to illegal trade and there are several factors that hinder the protection of the orangutan population, such as logging, encroachment and road network expansion. The illegal trade in orangutans is something that must be considered because the punishment imposed on the perpetrators is still too light, with what they are doing. Therefore, the punishment and fines can be heavier so that the perpetrators are deterred. Stop forest hunting by tightening forest guarding and providing education about protected animals to the community. Likewise in protecting animals in the country of Indonesia.Keywords: protection, orangutans, illegal trade